Dengue in Timor-Leste during the COVID-19 phenomenon - da Cruz, Zito Viegas; Araujo, Afonso Lima; Ribas, Alexis; Nithikathkul, Choosak (Frontiers in Public Health, 2023)
Abstract This study aims to identify dengue incidence rates at high geographical resolution using a geographic information system (Arc GIS software) during the COVID-19 phenomena in Timor Leste. Secondly, to determine the association between local environmental, sociodemographic, and geographic conditions and the transmission of the disease. A descriptive study using GIS was performed to provide a spatial-temporal mapping of dengue cases. Secondary data, which was sourced from the department of health statistics information system under the Ministry of health Timor Leste, was collected for the period during the COVID-19 outbreak in 2020–2021. This data was grounded at the municipality (district) level. Quantum GIS and Microsoft Excel were used to analyze the data. During the COVID-19 outbreak (2020–2021), dengue spreads over the country. In 2020, an increase in Dili municipality, the capital city, with dengue morbidity and mortality cases was reported more than twelve other municipalities. The high dengue cases were found in a municipality with an urban center and a high population density. In terms of severity, dengue fever (DF) is most commonly reported with a total of 1,556 cases and is followed by dengue hemorrhagic fever (DHF) and dengue shoch syndrome (DSS). The most cases were reported in the period of the monsoon season, such as December, January, and March. Dengue mapping using GIS is helpful to understand the disease presence and dynamic disease over time.